Role of chronic hepatitis in development of thalassaemic liver disease. Issue 9 (September 1976) - Masera, G; Jean, G; Gazzola, G; Novakova, M
Abstract : Liver function and the presence of HBsAg and anti-HBsAg were studied in 90 hypertransfused thalassaemic children. Increased serum transaminases were found in 62 patients, and persisted from more than 6 months in 45 cases. Liver biopsy in this latter group led to a diagnosis of 14 cases of chronic persistent hepatitis, 9 cases of aggressive hepatitis, and 3 cases of hepatic fibrosis. In Italy thalassaemic children undergoing hypertransfusion therapy frequently encounter SH virus infection, with a consequent hepatitis that is generally anicteric and unrecognized unless systematically sought. In a liver already stressed by the concomitant iron overload, hepatitis infection might thus play a key role in the evolution of cirrhosis which frequently affects thalassaemics.